FAKTOR-FAKTOR YANG MEMENGARUHI BEHAVIOURAL INTENTION PENGGUNAAN MOBILE WALLET SHOPEEPAY DI SURABAYA - Jacqualine Basary; Indarini; Andhy Setyawan (CALYPTRA, 2024)
Abstract—The rapid development of technology in developing countries has resulted in high growth in recent years. Coupled with the support of the internet and mobile phone networks that have changed people's habits, especially in payment methods that were originally in the barter system, money and nowadays called mobile wallets that are inherent and have many payment options with a single scan and are fast and precise. People will not feel worried about losing money in one hand in the form of a smartphone. and some smartphones are equipped with NFC (Near-Field Communication) chips that only need to be tapped to make payments. This research aims to understand the factors that influence the use to adopt ShopeePay mobile wallet in Indonesia. There are 190 questionnaire results collected from ShopeePay users in Surabaya, then the data is analyzed using the Structural Equation Model (SEM) with data processing using Analysis Moment of Structural (AMOS) software. The results of this study indicate that performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), perceived value (PV), perceived risk (PR), perceived trust (PT), perceived regulatory support (PRS), promotional benefits (PB) are proven to be factors that significantly influence behavioral intention (BI) of ShopeePay mobile wallet in Surabaya. Keywords: performance expectancy, behavioural intention, mobile wallet Abstrak—Perkembangan teknologi yang pesat di negara-negara berkembang telah menghasilkan prtumbuhan yang tinggi dalam beberapa tahun terakhir ini. Ditambah dengan dukungan jaringan internet dan mobile phone yang telah mengubah kebiasan orang apalagi dalam metode pembayaran yang dari awal dalam system barter, uang dan saat ini disebut mobile wallet yang sudah melekat dan memiliki banyak pilihan pembayaran dengan sekali scan dan cepat dan tepat. Orang-orang tidak akan merasa khawatir dengan kehilangan uang sudah cuku dalam satu genggaman dalam bentuk smartphone.dan beberapa smarthphone telah dilengkapi dengan NFC (Near-Field Communication) chip yang hanya perlu di tap untuk melakukan pembayaran. Penelitian ini bertujuan untuk dapat mengerti factor-faktor yang mempengaruhi penggunaan untuk mengadopsi mobile wallet ShopeePay di Indonesia. Terdapat 190 hasil kuesioner yang dikumpulakn dari pengguna ShopeePay di Surabaya kemudian data analisis menggunakan Structural Equation Model (SEM) dengan pengolahan data menggunakan software Analysis Moment of Structural (AMOS). Hasil penelitian ini menunjukan bahwa performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), perceived value (PV), perceived risk (PR), perceived trust (PT), perceived regulatory support (PRS), promotional benefits (PB) terbukti sebagai factor yang signifikan mempengaruhi behavioural intention (BI) mobile wallet ShopeePay di Surabaya. Kata Kunci: performance expectancy, behavioural intention, mobile wallet